Analyzing warehouse operations in a 3PL company - Mapping of processes and identification of key time drivers - Frankin, Sanne; Johannesson, Karolina (My University, 2013)
Warehouse operations in a 3PL company are often very specialized and customer unique. Thus, estimating the need for manual labor when designing new warehouse solutions can be a complex procedure. One of the main issues for Schenker Logistics when quoting future customers is to know the required blue-collar labor and how to distribute operators between inbound and outbound processes. The purpose of this Master’s thesis is to create a calculation tool that describes different time drivers in warehouse operations and facilitates estimations of required manual labor at Schenker Logistics. To fulfill this aim, two main sources of data were needed. Firstly, observations for five different types of customers were performed in order to gain deep understanding about inbound and outbound processes, which allowed the development of customer specific process maps. These acted as foundation when determining relevant standard processes, activities and tasks necessary for further observations and time recordings. Secondly, time studies were performed for the predetermined elements and the collected data was analyzed to identify significant time drivers. The results were used to develop a calculation tool that considers different arrays of data and factors to calculate the required manual labor, given customer specific inputs. The calculation tool was later tested in order to assess its validity and calculate time allowances, which are described together with general recommendations of improvements in current warehouse solutions in the final part of the thesis.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics